2018
DOI: 10.3341/kjo.2018.0044
|View full text |Cite
|
Sign up to set email alerts
|

Combination Surgery of Silicone Tube Intubation and Conjunctival Resection in Patients with Epiphora

Abstract: PurposeTo compare the success rates of performing only silicone tube intubation versus carrying out both conjunctival resection and silicone tube intubation.MethodsThe subjects of this study involved 62 patients (96 eyes) between October 2015 and May 2017 who were diagnosed as having punctal stricture or nasolacrimal duct stenosis. Out of 96 eyes, 47 underwent only silicone tube intubation, and 49 underwent both silicone tube intubation and conjunctival resection. Three parameters were measured at 1, 3, and 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…One of the study results reveled that application of silicon tube intubation showed higher rate of success in advance age group with mean age of 59.8±7.18 similar in present study. 1 Success rate was observed in given study in both group comprises of silicon tube intubation and dacryocystography with pre-operative syringing test were applied in advance age group, the mean age in sub groups were 62.3±10.9 and 58.6±10.3, that showed similar to our study results success rate of both procedure in adults and old age with minimal rate of complication and prolong follow up. 12 Similar to the present study the evidence of that study describe the success rate of silicon tube intubation in advance age group with free of symptoms and complications.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…One of the study results reveled that application of silicon tube intubation showed higher rate of success in advance age group with mean age of 59.8±7.18 similar in present study. 1 Success rate was observed in given study in both group comprises of silicon tube intubation and dacryocystography with pre-operative syringing test were applied in advance age group, the mean age in sub groups were 62.3±10.9 and 58.6±10.3, that showed similar to our study results success rate of both procedure in adults and old age with minimal rate of complication and prolong follow up. 12 Similar to the present study the evidence of that study describe the success rate of silicon tube intubation in advance age group with free of symptoms and complications.…”
Section: Discussionsupporting
confidence: 86%
“…Epiphora associated with multiple underlying causes such as trauma, radiotheraphy, burn or drugs had wide contribution. 1 The silicon tube was mainly presented by keth. Who applied the procedure in patient with nasolacrimal duct obstruction as an alternative of commonly used skills.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al . 23 compared the surgical outcomes of silicone tube intubation alone versus in combination with conjunctival resection in patients with NLD stenosis accompanied by conjunctivochalasis, and reported that the success rate, tear meniscus height, and patient’s satisfaction were all superior in the combined surgery group. To improve surgical outcomes after EDCR in older patients, simultaneous eyelid tightening procedure and/or conjunctival resection with EDCR may be helpful for the treatment of epiphora resulting from eyelid laxity, conjunctivochalasis and NLDO.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [23] compared the success rates of only silicone tube intubation with the combination of conjunctival resection and silicone tube intubation in patients with nasolacrimal duct obstruction. It was concluded that performing resection for the relaxed plica semilunares increases the success of silicone tube intubation.…”
Section: Discussionmentioning
confidence: 99%